Production of cellulolytic enzymes by Pleurotus species on lignocellulosic wastes using novel pretreatments - Singh, M. P.; Pandey, A. K.; Vishwakarma, S. K.; Srivastava, A. K.; Pandey, V. K.; Singh, V. K. (Cellular and Molecular Biology, 2014)
In the present investigation three species of Pleurotus i.e. P. sajor-caju (P1), P. florida (P2) and P. flabellatus (P3) along with two lignocellulosic substrates namely paddy straw and wheat straw were selected for evaluation of production of extracellular cellulolytic enzymes. During the cultivation of three species of Pleurotus under in vivo condition, the two lignocellulosic substrates were treated with plants extracts (aqueous extracts of ashoka leaves (A) and neem oil (B)), hot water (H) and chemicals (C).Among all treatments, neem oil treated substrates supported better enzyme production followed by aqueous extract of ashoka leaves, hot water and chemical treatment. Between the two substrates paddy straw supported better enzyme production than wheat straw. P. flabellatus showed maximum activity of exoglucanase, endoglucanase and Î²-glucosidase followed by P. florida and P. sajor-caju.